Comparative Study of Business Excellence Enablers between Small and Medium Enterprises and Multinational companies: A TQM Survey Result - Md Fauzi Ahmad; Shafeeka Fadlikh Zamri; Norhadilah Abdul Hamid; Ahmad Nur Aizat Ahmad; Nor Aida Abdul Rahman; Mohd Nasrun Mohd Nawi (International Journal of Supply Chain Management, 2019)
Business excellence (BE) model is a very crucial tool for organisations to improve their business performance. However, SMEs seems to face issues in implementing business excellence compared to MNCs due to less resources and exposure on BE. Thus, understanding the appropriate business excellence enablers to be implemented in order to achieve an outstanding performance is crucial for SMEs and MNCs. This study aimed to determine the level of business excellence enablers amongst SMEs and MNCs. There were six enablers utilized in this study which were; (1) Leadership, (2) Strategic Planning, (3) Customer Focus, (4) People, (5) Process, and also (6) Information. A total population of 100 respondents have been selected. Finally, 60 respondents have replied for further analysis. Random sampling technique was used during the distribution of questionnaires and SPSS was also applied in this study to analyse data and generate outcomes. Based on research outcomes, customer focus practices had the highest mean (Mean=6.29) which classified as high level. Furthermore, comparison analysis of BE enablers between SMEs and MNCs has been conducted. The result showed that there was no significant difference between SMEs and MNCs except information but MNCs mean ranks were higher compared to SMEs. This research study is also conducted as a guidance for both SMEs and MNCs to improve their business performances in the future.